The Social Determinants of Mental Health: Psychiatrists’ Roles in Addressing Discrimination and Food Insecurity - Shim, Ruth S. (Focus (Am Psychiatr Publ), 2020)
The social determinants of mental health are societal problems that disrupt optimal mental health, increase risk for and prevalence of mental illnesses, and worsen outcomes among individuals with mental illnesses. The various social determinants, two of which are described herein because they are too often neglected—discrimination and food insecurity—are underpinned by an unequal and unjust distribution of opportunity, which, in turn, is driven by both public policies and social norms. Discrimination and social exclusion, especially based on race and ethnicity, are pervasive and will remain largely resistant to change within society until explicitly antiracist public policy is enacted and overtly racist social norms are replaced by attitudes of acceptance and social inclusion. Similarly, eradicating food insecurity will occur only through changes in both policy and social norms. Psychiatrists have an opportunity to screen for, thoroughly assess, and address social risks (including perceived discrimination and food insecurity) at the clinical level. They also can play an important role in the shaping of policy and changing of social norms at the community and societal levels. All of these interventions and activities will ultimately improve mental health, reduce the prevalence of mental illnesses, and improve outcomes for patients.